Determinants of Efficiency of Islamic Commercial Banks in Indonesia - Dita Anggraini; Mohamad Irsyad (Transpublika Publisher, 2025)
Islamic banking plays a crucial role in Indonesia's economy and faces risks that impact the sustainability of bank performance as a mediator in the financial system. For the sake of the bank's sustainability, it is necessary to measure efficiency and control risk, measuring the level of efficiency is better than measuring profitability because it is measured by various outputs and inputs, so it does not only focus on company profits. This research aims to investigate the influence of NPF, FDR, BOPO, and CAR on the efficiency of Islamic commercial banks. The research employs quantitative techniques and is based on data obtained from the annual reports of Islamic commercial banks released by the OJK from 2019 to 2023. With the first test using DEAP (VRS) to assess the efficiency level of Islamic commercial banks, then measuring between variables using Eviews 12 (tobit regression). The sampling technique with purposive sampling (sample of 11 banks from 13 population banks). The results indicate that FDR positively impacts the efficiency of Islamic commercial banks, while CAR has a negative impact. However, NPF and BOPO calculations do not influence the efficiency of Islamic commercial banks. In summary, FDR positively affects efficiency, while CAR negatively impacts it in Islamic commercial banks, with NPF and BOPO having no effect.